RISK OF INJURY COMPARISON BETWEEN REGULAR AND KNUCKLE PUSH-UP BASED ON KINEMATIC PARAMETER ANALYSIS - Alvin Alvin; Moch Fakhrul Fauzi; Jihad Ibnu Zia; Eldita Fauzi Mukhtar; Eki Dwi Juliansyah Putra; Ferryanto Ferryanto (Jurnal Rekayasa Mesin, 2022)
Nowadays, it is difficult to access physical exercise facilities because people spent most of their time at work. Therefore, physical exercises that could be done with less equipment and space are more likely needed, and a push-up is one of them. There are several kinds of push-up which two are regular push-up and knuckle push-up. Both of them differ in hand posture, which carries a different risk of injury. In this research, kinematic parameters of joints on both of the push-up method that was acquired from optical motion capture using 120 fps GoPro camera and six markers were compared to identify which method would lead to a higher risk of injury. From analyzing the elbow joints acceleration, it was observed that the maximum value of both the linear and angular acceleration of knuckle push-up was larger. This means that the elbow joints suffered more load during knuckle push-up, leading to a higher risk of injury.